KORESPONDENCJA ELŻBIETY KRASIŃSKIEJ. ROZMYŚLANIE NAD SPOŁECZNYMI ROLAMI KOBIET W XIX W. JAKO EGO-DOKUMENT - Jeznach, Klaudia (Colloquia Litteraria, 2025)
The article analyses Elżbieta Krasińska’s correspondence in the context of ego-documents, focusing on the issue of femininity. A general outline of epistolography and research on ego-documents and women’s writing is followed by a detailed discussion of Krasińska’s letters, showing her changing perspective. These letters display emancipator aspirations, the desire for self-education and the need for women’s liberation, whilst on the other hand showing acceptance of traditional roles, such as the those of wife and mother. Analysis of the letters shows Krasińska construct her own ‘herstory’, negotiating between patriarchal expectations and the individual striving for autonomy.